Inclusió N School In The Regulations Under New Legal In Chile - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2020)
Nowadays, the link between concepts of education and diversity is very far in the schools of Chile, and even more so in the educational policies of the country, which only interests the concept of inclusion as a more segregating than inclusive concept. Three years after it was promulgated by President Michelle Bachelet, on Tuesday, March 1 of this year, the School Inclusion Law begins to be officially applied. Doubts, criticisms and marked differences persist from different sectors towards the new regulations that in principle intend to end profit, selection and co-payment in subsidized private education establishments and not to the integration and inclusion of students with SEN as the focus principal.